Obscure Rare Cause of Recurrent Angina in Post CABG Patient: Coronary-Subclavian Steal Syndrome - I. S. Monga; M. K. Yadav (National Board of Examinations Journal of Medical Sciences)
Coronary subclavian steal syndrome (CSSS) is a rare and unrecognized complication of coronary bypass grafting surgery when a left internal mammary artery (LIMA) graft is utilized for left anterior descending (LAD) artery revascularization without knowing left subclavian artery status. We describe a case of a 67-year-old male, with a known history of triple vessel coronary artery disease (CAD) managed with CABGx3 in March 2003. The patient presented after 16 years with complaints of recurrent angina for the past 15 years which aggravates on exertion, especially of left hand. Recurrent hospitalizations and repeated Coronary angiograms (CAG) as well as CT Coronary angiography failed to diagnose the cause of angina. Subclavian angiography and subsequent methodical clinical examination during the present admission revealed left subclavian origin stenosis which was successfully revascularized by deployment of a stent resulting in convincing relief in the patient’s angina.